2017
DOI: 10.1186/s13018-017-0648-2
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of the InterTan nail and proximal femoral nail anti-rotation in the treatment of intertrochanteric fractures in elderly patients with osteoporosis: a minimum follow-up of 3 years

Abstract: BackgroundThe study aims to compare the long-term functional and radiographic outcomes of two devices for the treatment of primary intertrochanteric fractures (IFs, OTA 3.1A2.1–A2.3) in elderly patients with osteoporosis.MethodsBetween December 2010 and August 2014, 332 elderly osteoporosis patients with IFs (OTA 3.1A2.1–A2.3) fixed by an InterTAN nail (IT) or a proximal femoral nail anti-rotation (PFNA) device were retrospectively evaluated. Follow-up occurred 1, 3, 6, and 12 months postoperatively and every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 24 publications
(32 reference statements)
3
52
1
2
Order By: Relevance
“…This may be related to InterTAN nails' ability to provide stronger fracture compression fixation. Furthermore, 4 of 6 studies showed significantly reduced postoperative pain in the InterTAN nail group compared to the PFNA group [23,[25][26][27]. The occurrence of screw cutout, femoral shaft fracture, and femoral head varus collapse inevitably increased the probability of reoperation, which was confirmed by this study in which InterTAN nail significantly decreased the risk of reoperation compared with the PFNA.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This may be related to InterTAN nails' ability to provide stronger fracture compression fixation. Furthermore, 4 of 6 studies showed significantly reduced postoperative pain in the InterTAN nail group compared to the PFNA group [23,[25][26][27]. The occurrence of screw cutout, femoral shaft fracture, and femoral head varus collapse inevitably increased the probability of reoperation, which was confirmed by this study in which InterTAN nail significantly decreased the risk of reoperation compared with the PFNA.…”
Section: Discussionsupporting
confidence: 71%
“…In total, 308 articles were initially collected from various electronic databases and managed using the Endnote X9, and 136 were excluded by preliminary screening; further careful screening of the full text excluded 161 articles leaving 9 studies for detailed evaluation. Nine studies (n=1332 patients) published between January 2013 and December 2019 that fulfilled the inclusion and exclusion criteria, including 2 RCTs and 7 observational studies [14,[21][22][23][24][25][26][27][28]. A total of 1332 patients were relatively evenly distributed in PFNA (n=681 patients) and InterTAN nail groups (n=651 patients), and the proportion of the two surgical procedures in A1, A2, and A3 fractures is 88/80, 479/460, 113/112, respectively.…”
Section: Baseline Characteristics Of Included Studiesmentioning
confidence: 99%
“…Several biomechanical and clinical data reported in the literature has shown favorable outcomes with the two-screw cephalomedullary nail construct [ 4 , 6 , 25 ]. Ruecker et al [ 9 ] looked at 100 patients with stable and unstable intertrochanteric fractures treated with this two-screw cephalomedullary nail construct and found no loss of reduction, non-unions, or implant failures.…”
Section: Discussionmentioning
confidence: 99%
“…We got satisfactory results with PFNA-2, and there was no considerable difference between 2 groups in terms of functional outcome. e varus collapse was seen in 12% [18], 5.8% [21], and 4.9% [22] of cases in previous studies. We got 15% cases with varus collapse with screw back out in the lateral entry group.…”
Section: Advances In Orthopedicsmentioning
confidence: 57%